2006
DOI: 10.1007/11753681_32
|View full text |Cite
|
Sign up to set email alerts
|

Design of Autonomous DNA Cellular Automata

Abstract: Abstract. Recent experimental progress in DNA lattice construction, DNA robotics, and DNA computing provides the basis for designing DNA cellular computing devices, i.e. autonomous nano-mechanical DNA computing devices embedded in DNA lattices. Once assembled, DNA cellular computing devices can serve as reusable, compact computing devices that perform (universal) computation, and programmable robotics devices that demonstrate complex motion. As a prototype of such devices, we recently reported the design of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Structural DNA nanotechnology has enabled the precise design of 2D and 3D static and dynamic structures including smiley faces, , twisted and bent bars, spheres, , linkages with complex motion, and nanorobots. Recent studies have demonstrated promising applications that utilize DNA origami nanostructures as templates to organize proteins or nanoparticles , in 2D and 3D space, vehicles for drug delivery, ,, nanopores, and biosensors. , Although the majority of DNA nanostructure applications utilize objects with static geometry, important strides have been made to design dynamic DNA devices (i.e., DNA nanomachines). Early DNA nanomachines involved configurations of DNA strands that could be triggered to undergo conformational changes, usually via DNA strand displacement, to achieve, for example, rotational or translational motion or even measure molecular binding energies . The development of scaffolded DNA origami ,, enabled greater control over geometry and stiffness of nanostructure components, which has expanded the possibilities to design complex mechanical behavior.…”
mentioning
confidence: 99%
“…Structural DNA nanotechnology has enabled the precise design of 2D and 3D static and dynamic structures including smiley faces, , twisted and bent bars, spheres, , linkages with complex motion, and nanorobots. Recent studies have demonstrated promising applications that utilize DNA origami nanostructures as templates to organize proteins or nanoparticles , in 2D and 3D space, vehicles for drug delivery, ,, nanopores, and biosensors. , Although the majority of DNA nanostructure applications utilize objects with static geometry, important strides have been made to design dynamic DNA devices (i.e., DNA nanomachines). Early DNA nanomachines involved configurations of DNA strands that could be triggered to undergo conformational changes, usually via DNA strand displacement, to achieve, for example, rotational or translational motion or even measure molecular binding energies . The development of scaffolded DNA origami ,, enabled greater control over geometry and stiffness of nanostructure components, which has expanded the possibilities to design complex mechanical behavior.…”
mentioning
confidence: 99%
“…An elementary CA with the programmable rule 90 has already been implemented with DNA tiles 31,32 albeit not in a way that permits inputs from an organizer. Other DNA-based implementations, which are more complex but offer more flexibility, have also been proposed 10 . On the basis of these proposed designs, a biomolecular CA that allows for input signals controlling its patterning process could be implemented as described in Suppl.…”
Section: Discussionmentioning
confidence: 99%
“…Such models would provide a conceptual framework for programmable pattern formation, and could reveal design principles, e.g., for synthetic molecular systems. DNA-based molecular systems, in particular, are readily programmable via the sequence-dependent interaction between DNA strands, which has been exploited to design self-assembling dynamic DNA devices 7 , neural network-like molecular computation 8 , coupled regulatory circuits 9 , and schemes for constructing molecular-scale cellular automata 10 . Here, we use a minimal model to study the concept of programmable pattern formation using theoretical and computational tools.…”
Section: Introductionmentioning
confidence: 99%
“…Biomolecular computation ventured into the domains of game theory, neuroscience and design automation to investigate utilization aspects such as RNA solutions to chess problems (Faulhammer et al, 2000), experimental DNA neural computation (Mills et al, 2001) and bottom-up circuit patterning based on DNA self-assembly (Dwyer, 2005). Other prominent developments were autonomous DNA nanomechanical computation and motion devices (Yin et al, 2005), as well as autonomous DNA cellular automata (Yin et al, 2006). The challenges and applications for selfassembled DNA nanostructures were thoroughly reviewed in (Reif et al, 2001).…”
Section:  Interactive Turing Machines With Advice and Infinity Of Op...mentioning
confidence: 99%